Administrative competencies and performance evaluation for the heads of Iraqi clubs from the point of view of members of the administrative bodies, a survey - Al-Dabbagh, ZubaidahAbdulwahab (International Journal of Psychosocial Rehabilitation, 2020)
Sports is a social movement that comes at the top of social organizations that enjoy advantages and peculiarities that are unique to them from other social systems, and in order for sports to keep pace with the development taking place in various areas of life and to bring about the desired state of change, it is necessary to provide and prepare conscious and efficient leaders to manage the sports movement after the movement has become Sports are broad and comprehensive, in which many work and supervise huge groups of members of society and are served by large and complex institutions and organizations that require knowledge and awareness of the foundations, functions and ways to achieve the desired goals through the joint work of individuals in sports institutions.